Alimentação e saúde: a dieta dos enfermos da Santa Casa de Misericórdia de Vila Rica (1793-1796) - Adriana da Costa Vieira (2014)
Diet of the Sick, Vila Rica, Hospital Santa Casa Misericordia, eighteenth century. The historiography of "Minas Gerais", which discusses the thematic of food is still quite incipient and the scarcity is even greater when searching for on the colonial. This paper discusses the diet of the unhealthy of the Santa Casa de Vila Rica Hospital, between 1793 and 1796. In modern times, the hospital diet was elected as a factor worthy of attention, and changed from simple and frugal to nutritious and therapeutic, defined according to the precepts of the hippocratic-galenic medicine. The research was developed from the survey of the remaining ancient lists of old recipe books and hospital expenses, consulted in the public archives and medical manuals published in the context from that time, as well as theoretical reasons to seek authors who explore the theme feeding at the "Minas Colonial". Our main targets were to identify which foods were the most commonly prescribed in the diet of the sick, exam in if the use of any food in the diet had a relationship with a particular historical period, and, finally, reflect if, with the aid of a nutritious and therapeutic diet, the hospital procedures took care simultaneously of the healing and the poverty.